PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MELALUI PENDEKATAN PAIKEM METERI DENAH DI KELAS III UPTD SD INPRES OETETE 2 - Lebertina Laitabun, Meilien; Maxsel Koro; Martha Khristina Kota (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study, entitled "Improving Creative Thinking Skills Through the PAIKEM Approach on Floor Plan Material for Grade III Students at UPTD SD Inpres Oetete 2," aims to enhance the creative thinking abilities of third-grade students by implementing the PAIKEM learning approach in Science and Social Studies (IPAS). Utilizing Classroom Action Research (CAR) across four sequential phases planning, acting, observing, and reflecting this study involved all 23 third-grade students at UPTD SD Inpres Outate 2, consisting of 15 male and 8 female students. Data were gathered through observation, testing, and documentation using Likert scales, test sheets, and observation forms, which were then analysed using a combination of descriptive quantitative and descriptive qualitative techniques. The findings revealed that the classical student mastery rate in Cycle I reached 43.48% (10 students passing) with a class average score of 66.74, which then significantly improved in Cycle II to 86.65% with 20 students achieving mastery. Consequently, these results demonstrate that the PAIKEM approach is highly effective in fostering students' creative thinking skills regarding floor plan material in Grade III at UPTD SD Inpres Oetete 2. Keywords: Creative Thinking Skills, Science and Social Studies Subject, and PAIKEM Approach